Analyzing Co-Creation Process in Cluster Industry using Agent-Based Simulation, Case Study : Cluster Industry Batik Solo - Putro, Utomo Sarjono; Hermawan, Pri; Utomo, Dhanan Sarwo; Nuraeni, Shimaditya; Ariyanto, Khrisna (SBM ITB, 2013)
At the beginning of 2008, the amount of cluster industry batik in Solo start to grew, with so many innovations, big market (co1nsumers), low cost and high progit margin. The condition is so much different compare to the late 1980. Thus, with agent-based simulation for industrial cluster, the aims of the research are to understand what mechanism can describe the formation of cluster industry batik in Solo, and propose strategies to stimulate formation of cluster industry.Â There are three agents modeled in the simulation; consumer, produce, and supplier. Each agent has their own attributes and decision role. As result, the simulation can describe that industrial cluster is formed as bottom-up interaction between agents with interdependency decision-making. In the long term, only producer agent that agglomerate with other industry can survive and the average wealth of each agent will increase along with the density cluster of certain industrial cluster. Several policies can be implemented to stimulate the industrial cluster formation are creating join-showroom, build waste-water treatment for several industries, renovate the facilities (access) to the cluster industries.Keywords:service science, cluster industry, agent-based simulation, cluster industry batik Solo